Challenges and Opportunities for Computer Media Integration in Early Childhood Learning Activities - Suprijanto, Agus; Nasution, Sri Purwanti; Kuswanto, Cahniyo Wijaya (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study aims to comprehensively analyze the challenges and opportunities of integrating computer media in early childhood education (ECE) through a systematic literature review of 25 scholarly articles and documents published between 2014 and 2024. Data were gathered from targeted searches on Google Scholar, DOAJ, and Scopus. The review identified five major themes: infrastructure readiness, teacher competence, parental roles, the impact on child development, and policy support in education. The findings indicate that while computer media have the potential to enhance the quality of ECE, implementation remains suboptimal due to gaps in facilities, low digital literacy among teachers, and the absence of targeted policy strategies. The study emphasizes that successful integration of computer-based media in ECE requires more than just providing technological tools; it necessitates a systemic and holistic approach. Strengthening human resource capacity, ensuring equitable access to infrastructure, and developing a technology-integrated curriculum should be prioritized. The findings suggest that if educators, families, and policymakers collaborate effectively, computer media can support adaptive, contextual, and sustainable learning strategies in ECE. Therefore, stakeholders must invest in comprehensive training, infrastructure development, and cross-sector collaboration to maximize the impact of digital media on young children’s learning experiences.